Pickering emulsions as an effective route for the preparation of bioactive composites: A study of nanocellulose/polyaniline particles with immunomodulatory effect - Korábková, Eva; Kašpárková, Věra; Vašíček, Ondřej; Víchová, Zdenka; Káčerová, Simona; Valášková, Kristýna; Urbánková, Lucie; Vícha, Jan; Münster, Lukáš; Skopalová, Kateřina; Humpolíček, Petr (Carbohydrate polymers, 2024)
Several studies have reported on application of cellulose particles for stabilizing Pickering emulsions (PE). Here we employ an original approach that involves using these particles as a part of advanced composite colloids made of conducting polymer polyaniline (PANI) and cellulose nanocrystals (CNC) or nanofibrils (CNF). PANI/cellulose particles were prepared using oxidative polymerization of aniline in situ in the presence of CNC or CNF. The type and amount of celluloses (CNC vs CNF) and concentration of precursors (aniline monomer and oxidant) used in the reaction determined properties of the colloidal particles, such as size, morphology and content of PANI. The particles demonstrated intriguing biological characteristics, including no cytotoxicity, antibacterial activity against Staphylococcus aureus and Escherichia coli, antioxidant activity and related immunomodulatory activity. For the first time, such composites were used to successfully stabilize oil-in-water PE with undecane or capric/caprylic triglyceride oils. The properties of the emulsions were determined by the PANI/cellulose particles and oil used. The key finding of the study is the demonstrated ability of PANI/cellulose particles to stabilize PE, as well as the excellent antioxidant activity and ROS scavenging action originating from PANI presence, indicating potential of such systems for use in biomedicine, particularly for wound healing.
Keywords: Oils; emulze; Cellulose; Aniline Compounds; aniliny; Emulsions; antioxidancia; Escherichia coli; oleje; Antioxidants; celulosa